Developing Adobe Flash Media with Android-Based to Improve Students’ Learning Outcome in Anti-Lock Brake System - Satria, Anas; Widjanarko, Dwi; Anis, Samsudin (Universitas Negeri Semarang, 2023)
The development of technology in education helped to increase learning quality. Existing developments required the world of education to adapt. Students' characterization in the XXI century was a generation that was closed to digitalization, so the teacher had to understand that learning media at school must carry out advanced technology. Specifically, the research purpose was: to develop media with adobe flash, to dig up the feasibility of learning media in the competency of an anti-lock brake system, and to know the improvement of learning outcomes in an anti-lock brake system. This research applied the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis consisted of determining the feasibility of learning media and deciding the media effectiveness. The feasibility test showed that the media was very feasible. The developed media was tested by N-Gain and got the effectivity until 76%, or it can be declared effective since t-count 18.13t-table, and Ha was accepted while H0 was refused. It can be concluded that adobe flash media with android-based can improve students' learning outcomes, especially in the Anti-Lock Brake Sistem at XII TKRO 1.